Korelasi gaya kepemimpinan terhadap kinerja federasi olahraga - Nugroho, Priyo Puji; Rustiadi, Tri; Castyana, Billy (Universitas Nusantara PGRI Kediri, 2022)
The achievement of organizational goals shows the performance of effective sports organizations, where the strategies taken by leaders in running the organization have a role. This quantitative study uses a cross-sectional survey approach to collect data in a month to understand the relationship between leadership style and sports federation performance. Due to time constraints, the population of this study was only focused on members of the 46 elite sports federations in Central Java Province. Using purposive sampling as a sampling technique and obtained 127 respondents. Using the Guttman scale, the respondent filled out the questionnaire related to the humanistic, transformational, participatory, servant, and organizational performance leadership styles. Based on the results of data analysis, it was found that the four leadership styles have a positive relationship where if the leadership style is often used in organizational management, organizational performance will also increase as the servant leadership style is the highest correlation level among others though it is not the most widely used leadership style by elite sport federation leaders in Central Java Province. The servant leadership style is only used by 96.61% of sport federation leaders, but 98.95% of leaders use the participative or democratic style.